2022
DOI: 10.1021/acsomega.2c01664
|View full text |Cite
|
Sign up to set email alerts
|

High Performance of Carbon Monoxide Gas Sensor Based on a Novel PEDOT:PSS/PPA Nanocomposite

Abstract: In this work, the carbon monoxide (CO) detection property of poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate)/poly( p -anisidine) (PEDOT:PSS/PPA) nanocomposite was systematically investigated at room temperature. The PEDOT:PSS/PPA nanocomposite was synthesized by the cost-effective “in situ chemical oxidation polymerization” technique. The electric, optical, spectroscopic, and structural properties of the as-prepared nanomaterials were analyzed with I – … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…The linear I-V curve indicated that the current conduction is mainly enforced by the bulk sensing material instead of Schottky contacts. 39,40 Different gases have different response characteristics towards a particular material. First, we observed the influence of various gases (CO, C 2 H 5 OH, SO 2 , NO 2 , H 2 S, NH 3 and CO 2 ) on the gas sensing performance of the NFP sensor in prospect of variation in electrical resistance at room temperature ( 27 1C).…”
Section: Gas Sensing Studiesmentioning
confidence: 99%
“…The linear I-V curve indicated that the current conduction is mainly enforced by the bulk sensing material instead of Schottky contacts. 39,40 Different gases have different response characteristics towards a particular material. First, we observed the influence of various gases (CO, C 2 H 5 OH, SO 2 , NO 2 , H 2 S, NH 3 and CO 2 ) on the gas sensing performance of the NFP sensor in prospect of variation in electrical resistance at room temperature ( 27 1C).…”
Section: Gas Sensing Studiesmentioning
confidence: 99%
“…15,23 To further analyse the reaction mechanism of AC within PEDOT:PSS, we acquired Fourier transform infrared (FTIR) spectra of the films. The band at about 833 cm −1 , attributed to the C–H group on the benzene ring, 24 exhibited a positive shift of 5 cm −1 , while that at about 1528 cm −1 from the sulfonate group of PSS 25 showed a negative shift of 12 cm −1 , upon AC modification (Fig. 1g–h).…”
mentioning
confidence: 92%
“…Conducting polymers and 2D carbon materials are gaining attention as CO gas sensor elements due to their high conductivity, larger surface area, and unique sensing mechanisms involving “chemical doping” or “charge transfer”. These properties enable operation at low and room temperatures, making them advantageous. ,,, Despite these benefits, most studied CO sensors using these materials, including commercial models like MQ-7B, MQ-9B, MP-7, MP-9, and GM-702B from Winsen, remain at the ppm level. The lamellar structure of 2D carbon-based materials like graphene allows direct interaction with the target gas, affecting CO sensor sensitivity through gas absorption and charge transfer .…”
Section: Introductionmentioning
confidence: 99%